2013
DOI: 10.1080/00150193.2013.821859
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Na0.5Bi0.5TiO3Thin Films with BaTiO3Buffer Layer (Study of Au/Na0.5Bi0.5TiO3/BaTiO3/Pt Capacitor)

Abstract: Lead free bilayer capacitor structure has been fabricated as a combination of sodium bismuth titanate (Na 0.5 Bi 0.5 )TiO 3 (NBT) thin films with barium titanate, (BaTiO 3 ) (BT) buffer layer in situ using pulsed laser deposition (PLD). PLD control parameters have been optimized using Taguchi approach to obtain good quality NBT and BT thin films. It has been observed that dielectric properties of NBT thin films enhanced by inserting BT buffer layer. This improvement in the dielectric properties of NBT thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The 600 1C (the lowest growth temperature in this work) films show the highest ON/OFF ratio with the best device uniformity. The minimum growth temperature of 600 1C that we tried in our work is within the optimum growth temperature (600-650 1C) reported in many works for PLD growth of NBT films 48,61,62 (although one study reported a substrate temperature of 550 1C, where they used a lower oxygen pressure during deposition 36 ).…”
Section: Resultssupporting
confidence: 69%
“…The 600 1C (the lowest growth temperature in this work) films show the highest ON/OFF ratio with the best device uniformity. The minimum growth temperature of 600 1C that we tried in our work is within the optimum growth temperature (600-650 1C) reported in many works for PLD growth of NBT films 48,61,62 (although one study reported a substrate temperature of 550 1C, where they used a lower oxygen pressure during deposition 36 ).…”
Section: Resultssupporting
confidence: 69%